Compressible Co3O4@MoS2 Aerogel as an Advanced Functional Electrode for Asymmetric Supercapacitors - Asgaran, Sohrab; Moazzami Goudarzi, Zahra; Pietrzyk-Thel, Paulina; Banti, Boka Fikadu; Osial, Magdalena; Michalska, Monika; Warczak, Magdalena; Gniadek, Marianna; Lee, Jaebeom; Giersig, Michael; Nwaji, Njemuwa (ACS applied materials & interfaces, 2025)
For the development of next-generation portable energy storage devices, compression-tolerant electrodes are essential, but most of the previous reports have focused only on carbon-based materials. Herein, gelatin methacrylate (GelMA) and poly(N-isopropylacrylamide) (PNIIPAM) were used as hosts to incorporate the Co3O4@MoS2 aerogel (Co3O4@MoS2 AG). GelMa-PNIPAM (GP) was transformed into a carbon network as an intrinsically compressible host template with high conductivity. The as-prepared electrode possesses a reversible compressive strain of 80% with excellent durability. Density functional theory (DFT) calculations show that the Co3O4@MoS2-AG heterostructure exhibits high electronic conductivity, low adsorption energy for OH- ions, and fast electron transfer capacity, which enhance the electrochemical performance with a high specific capacitance of 1026.9 at 1 A g-1 and a remarkable cycling stability of 80.8% after 10,000 charge-discharge cycles. Besides, the assembled asymmetric supercapacitor based on compressible Co3O4@MoS2 AG/RGO exhibits a stable energy storage performance under different compressive strains and after 100 compression-release cycles. The results of this study demonstrate the potential of a metal-based electrode with high energy storage properties for wearable devices.
Keywords: MoS2; asymmetric supercapacitor; compressible electrode; Co3O4; aerogels